2015
DOI: 10.11118/actaun201563031031
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Consumer Behavior: Use of Association Rules

Abstract: This paper focuses on problematic of use of association rules in exploring consumer behavior and presents selected results of applied data analyses on data collected via questionnaire survey on a sample of 1127 Czech respondents with structure close to representative sample of population the Czech Republic. The questionnaire survey deals with problematic of shopping for meat products. The objective was to explore possibilities of less frequently used data-mining techniques in processing of customer preference.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This research uses several aspects or attributes such as teaching learning, tutoring, and consulting, research and community service, and other tasks beyond the main task as a consideration in judgment Subsequent research that utilizes the Rough Set method, which uses a variable of education, academic position and Department of office is then used to determine the desired rector candidate in accordance with the existing provisions. The results of the study show that education is a major factor in the election of foreign rector which is then supported by the academic position and structural department owned by the lecturer (Chen et al, 2020;Turčínek and Turčínkova, 2015;Dhandayudam and Krishnamurthi, 2013;Shyng et al, 2007;Suchacka and Chodak, 2017;Sembiring and Azhar, 2017;Hadiansah, 2017;Wang and Chou, 2013;Sanny, Susastra, Roberts, and Yusramdaleni, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…This research uses several aspects or attributes such as teaching learning, tutoring, and consulting, research and community service, and other tasks beyond the main task as a consideration in judgment Subsequent research that utilizes the Rough Set method, which uses a variable of education, academic position and Department of office is then used to determine the desired rector candidate in accordance with the existing provisions. The results of the study show that education is a major factor in the election of foreign rector which is then supported by the academic position and structural department owned by the lecturer (Chen et al, 2020;Turčínek and Turčínkova, 2015;Dhandayudam and Krishnamurthi, 2013;Shyng et al, 2007;Suchacka and Chodak, 2017;Sembiring and Azhar, 2017;Hadiansah, 2017;Wang and Chou, 2013;Sanny, Susastra, Roberts, and Yusramdaleni, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…To the best of the authors' knowledge, although association rule mining has not been applied in the fruit market, it has been widely used to analyze consumer preferences in other fields (Guan et al, 2018;Park and Kim, 2018;Wang, 2019). Further, Tur cínek and Tur cínkov a have also confirmed that the application of association rule mining in customer research can provide more insights and good supplementary analysis related to consumer data exploration, which makes it possible to compensate for the defects of BWS, descriptive statistics and hypothesis testing (Tur cínek and Tur cínkov a, 2015). Based on this, in the present study, association rule mining is applied to analyze the preferences of fruit consumers.…”
Section: Introductionmentioning
confidence: 90%
“…When dealing with a website, refs. [18,33] applied clustering algorithms to review the relationship between predicted consumer and product characteristics. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%